2016
DOI: 10.1038/ejcn.2016.80
|View full text |Cite
|
Sign up to set email alerts
|

Perception of lactose intolerance impairs health-related quality of life

Abstract: Subjective perception of lactose intolerance affects the decision to avoid dairy even more than objective malabsorption. However, both self-perception of lactose intolerance and objective lactose malabsorption are associated with poorer perceived quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Two studies reported on the impact of lactose intolerance on the quality of life. In one study, the self-perception of intolerance was associated with lower health-related quality of life scores (median: 60 vs. 70, p < 0.01) [56]. In contrast, another survey did not find a negative impact of being intolerant to lactose on this score [57].…”
Section: Health Aspects Of Lactose-free Dairymentioning
confidence: 99%
“…Two studies reported on the impact of lactose intolerance on the quality of life. In one study, the self-perception of intolerance was associated with lower health-related quality of life scores (median: 60 vs. 70, p < 0.01) [56]. In contrast, another survey did not find a negative impact of being intolerant to lactose on this score [57].…”
Section: Health Aspects Of Lactose-free Dairymentioning
confidence: 99%
“…In Australia, dairy avoidance may be practiced by 17% of the population, of whom the majority (13%) avoid dairy on the basis of self-reported negative reactions to dairy products ( 1 ). This trend is evident globally ( 2 , 3 ), where perceived or actual intolerance to cow milk (CM)—either due to lactose or other components of milk ( 4 )—influences consumption behaviors ( 5 , 6 ). Dairy products are recognized as an important source of nutrients ( 7 , 8 ), including calcium and high quality protein ( 7 ), essential for growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…The general assumption surrounding the milk intolerance syndrome is that it is triggered by lactose malabsorption [ 42 , 43 ]. However, as described in the 2010 National Institutes of Health Consensus statement on lactose intolerance, many who suffer from self-reported gastrointestinal (GI) issues display no evidence of insufficient lactase enzyme activity [ 44 ].…”
Section: Introductionmentioning
confidence: 99%